The Effects of Nb Addition on the Microstructure and Mechanical Properties of Melt Spun Al-7075 Alloy - Kilicaslan, Muhammed Fatih; Elburni, Saad Ibrahim; Akgul, Bekir (Walter de Gruyter GmbH, 2021)
Abstract The mechanical properties of the Al-7075 material, which is used in important areas such as automotive, aviation and defense industry, are still being studied by researchers. In this study, the effects of different proportions of Nb additives on the microstructure and mechanical properties of the rapidly solidified Al-7075 alloy was investigated. Rapid solidification processes were carried out with a single roller melt spinner at a disk surface speed of 25 m / s. Microstructure characterization was performed by using a scanning electron microscopy (SEM) and X-ray diffraction. According to the results, the Nb additive significantly increased the micro hardness of the Al-7075 alloy. The microhardness of the sample added with 0.5% by weight of Nb is 0.9 GPa. This value is 3 times higher than the sample without Nb added. The Nb contribution has led to modification of the dimensions and shapes of both α-Al and intermetallic phases. Nb addition reduced the average grain size from 9.1 µm to 2.46 µm.
Keywords: 7. Clean energy